The effect of changing-elasticity on the stress concentration near a semi-infinite crack tip (MAUSAM, 1979)
One of the very convincing premonitory changes in earthquake predictions concerns the variation of the velocity ratio (Vp/Vs) preceding the occurrence of the event. The aim of the present investigation is to construct a, the radical basis to evaluate the consequences of such changes on, say, the stress concentration near an already existing fault with a given static initial field. The change in elasticity is assumed over a limited part of the where  the medium near the fault.